Ecological aspects of Lebiasina erythrinoides (Characiformes: Lebiasinidae) from an andean piedmont stream in Colombia - Javier Alejandro Maldonado Ocampo; Alexander Urbano Bonilla; Jhon Zamudio (Universitas Scientiarum)
The present study describes ecological aspects of Lebiasina erythrinoides; 200 individuals were sampled throughout an annual hydrological cycle from October 2008 to September 2009 in La Calaboza stream, a Piedmont tributary of the Rio Cravo Sur. The studied population had more females than males (1.5:1) and preferred habitats dominated by shoreline vegetation and rocky substrates. Prior to reproductive events, individuals presented an increase in the condition factor (K) and the gonosomatic index (GSI). On average, 648.8 oocytes are discharged twice a year: at the beginning of the rainy season, and during falling water phase. The mean sizes at sexual maturity found for females were 73.5 mm standard length (SL) and for males 70 mm SL. Rounding up, an average minimum size of capture of 75 mm SL is proposed. Most specimens of the population (65 %) were found to be maturing or mature (stages II and III), 28.5 % immature (stage I), 5.0 % in post reproduction stage V, and 1.5 % in reproductive phase (IV). Results suggest this species is omnivorous with a preference for invertebrates (IRI = 41.2 %) and vegetal material (IRI = 27.8 %), but also includes a variety of other items. The values of the diet are correlated with hydrological cycle and size.